Playing games in nineteenth-century Britain and America - Hawkins, Ann R.; Bistline, Erin N.; Blackwell, Catherine S.; Ives, Maura C., 1960- (SUNY series, studies in the long nineteenth century., 2021)
"This book illuminates the ways that games--from baseball cards to board games, poker to boxing, and croquet to strategies of war -- were integral to nineteenth-century life and culture in the US and UK"--